Emodin inhibits colon cancer tumor growth by suppressing tumor cell glycolysis through inhibition of NAT10-mediated PGK1 ac4C modification - Wei, Zhuoxin; Lv, Zhuo; Zhang, Weimin (Frontiers in Oncology, 2025)
IntroductionInhibition of glycolysis represents a potent therapeutic approach for colon cancer. Emodin, a natural plant-derived compound with anticancer properties, has shown efficacy in cancer treatment. NAT10 promotes cancer progression by catalyzing ac4C production on mRNAs, but it remains unclear whether emodin regulates glycolysis in colon cancer cells by targeting NAT10. This study aimed to investigate the role of emodin in glycolysis regulation in colon cancer and its underlying mechanisms. MethodsGlycolysis was assessed by measuring cell proliferation, glucose uptake, lactate production, and extracellular acidification rate. The ac4C levels and NAT10 expression were measured by dot blot and quantitative real-time PCR. The underlying mechanism was investigated by methylated RNA immunoprecipitation (MeRIP), RIP and dual luciferase reports. The effect of emodin on tumor growth in vivo was evaluated by hematoxylin and eosin staining and immunohistochemistry staining.ResultsResults showed that emodin inhibited glycolysis in colon cancer cells in a dose-dependent manner, and suppressed the ac4C levels and NAT10 expression of cells. Moreover, NAT10 overexpression restored glycolysis in colon cancer cells inhibited by emodin. Mechanistically, NAT10 promotes glycolysis of colon cancer cells by stabilizing PGK1 expression through enhancing ac4C modification on PGK1. In vivo experiments suggested that emodin inhibited colon cancer tumor growth, as well as NAT10 and PGK1 expression. DiscussionIn conclusion, we demonstrated that emodin inhibited tumor growth of colon cancer by suppressing glycolysis in tumor cells through inhibiting NAT10-mediated ac4C modification of PGK1, indicating that emodin is an effective medicine for treatment of colon cancer.